The role of lean six sigma in driving sustainable manufacturing practices: an analysis of the relationship between lean six sigma principles, data-driven decision making, and environmental performance - Huang, Jing; Irfan, Muhammad; Fatima, Syeda Saman; Shahid, Rao Muhammad (Frontiers in Environmental Science, 2023)
In the competitive manufacturing world, companies constantly seek innovative approaches to improve operations, remain competitive, and promote sustainability. One such approach gaining popularity is the Lean Six Sigma methodology, which has positively impacted environmental performance. This paper examines the relationship between Lean Six Sigma methodology, data-driven decision-making, and sustainable manufacturing practices in the manufacturing industry. Thematic analysis was conducted to identify key principle nodes, including Six Sigma, quality, quality improvement, approach, manager, and front-line worker. Employee motivation, balanced scorecards, company culture, CRM, and data-driven decision-making were critical factors driving sustainable manufacturing practices. Findings suggest that implementing Lean Six Sigma methodology, promoting data-driven decision-making, and fostering a positive company culture are effective strategies for improving environmental performance in the manufacturing industry. The results of this analysis offer valuable insights for manufacturing companies seeking to improve their sustainability practices while remaining competitive in the marketplace.